Determining the Factors of Social Phobia Levels of University Students: A Logistic Regression Analysis - Hamit Ozen (ÜNİVERSİTEPARK Limited, 2016)
Experiencing social phobia is an important factor which can hinder academic success during university years. In this study; research of social phobia with several variables is conducted among university students. The research group of the study consists of total 736 students studying at various departments at universities in Turkey. Students are divided into two groups, as low and high level positive evaluation fear (PEF) as measured by the Positive Evaluation Fear Scale (PEFS). In respect to Odds rates, the most crucial factor about PEF of students is the time spent daily on the internet. Students who spend their time on the internet have PEF 2.4 times more than those who do not. As a secondary important factor according to negative evaluation fear scale (NEFS), students consider the home city where they lived before attending university increases phobia 30% more than the rate of people who think otherwise. Thus, results showed that spending long hours on the internet and home city lived in before university are significant factors resulting in social phobia.